The effect of silica-enriched rice husk biochar and NPK fertilizer on soil total nitrogen, nitrogen uptake, and yield of lowland rice - Sofyan, Emma Trinurani; Mulyani, Oviyanti; Citraresmini, Ania; Rachmadi, Meddy; Livia, Kharmelia Sandra (Kultivasi, 2026)
Rice production in Indonesia increasingly relies on agricultural intensification, which can accelerate soil degradation and reduce fertilizer-use efficiency. Therefore, sustainable soil management is needed to maintain soil fertility. Silica-enriched rice husk biochar (biochar-silica) is a promising soil amendment because it improves soil properties and nutrient retention. This study evaluated the effects of biochar-silica and NPK fertilization on soil total nitrogen, nitrogen uptake, and yield of lowland rice (Oryza sativa L.). The experiment was conducted from September 2025 to January 2026 using a two-factor randomized block design with nine treatment combinations and three replications. The treatment consisted of three levels of amendment (0 t biochar ha−1; 1.25 t biochar ha−1 + 160 kg SiO2 ha−1; 2.5 t biochar ha−1 + 320 kg SiO2 ha−1) and three levels of NPK fertilizer application (0 kg urea ha−1 + 50 kg SP-36 ha−1 + 37.5 kg KCl ha−1; 100 kg urea ha−1 + 50 kg SP-36 ha−1 + 37.5 kg KCl ha−1; 200 kg urea ha−1 + 100 kg SP-36 ha−1 + 75 kg KCl ha−1). Significant interaction effects were observed on soil total nitrogen, harvested dry grain yield, and milled dry grain yield, whereas nitrogen uptake was significantly affected only by NPK fertilizer application. Under the experimental conditions, the interaction between biochar-silica and NPK fertilizer application resulted in soil total nitrogen to 0.42% and milled dry grain yield to 6.63 t ha⁻¹. These findings demonstrate that integrating biochar-silica with NPK fertilizer application can improve soil nitrogen status and support lowland rice production.